(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is interested in the role played by entrepreneurship education (EE) in the area of digital entrepreneurship. The researchers explored the relationships between the external enabler mechanisms (EEMs) in the digital environment and online collaborative learning (OCL), and their impact on entrepreneurial intention (EI). To test these relationships, the researchers developed an OCL program called Digital Business Management, which consisted of six modules on digital knowledge to be studied over 12 weeks. The participants in this study were students from two different batches of the program who studied in the same year in Thailand. The profiles of the students were a heterogeneous mixture of entrepreneurs and individuals in other careers. The data were collected at the end of the final class for each batch. We applied the quantitative method by using linear regression as the statistical method. The findings showed that OCL serves as a partial mediator between the EEMs in digital entrepreneurial intention (DEI). This finding supports the idea that EE is an important linkage between the external enablers and EI, and that OCL is an effective alternative method of delivering EE.